Brand and Value Co-Creation: A Stakeholder Approach to Ottawa's CFL Expansion Franchise - Rodrigue, Francois (Université d'Ottawa / University of Ottawa, 2014)
This study intended to advance the understanding of brand and value co-creation in sport management. A single exploratory case study of the Ottawa REDBLACKS, the CFL expansion franchise launching in 2014, was conducted. The purpose of the research was to unveil the practices that could lead to brand and value co-creation in the relationships between the Ottawa REDBLACKS and their stakeholders. Semi-structured interviews were performed with 20 participants from the focal organization’s network of stakeholders. The sample was built through a purposeful and snowball sampling method that added to stakeholders identified from the literature. Archival data of media publications, organizational online content, and radio podcasts were also gathered in order to complement the data from the interviews. The deductive and inductive data analysis highlighted five main practices that could lead to brand or value co-creation in the stakeholder-firm relationship performance in a unique sport context: establishing relationships, supporting public relations, sharing resources, enhancing the experience, and driving brand image. The findings explained that joint actions between stakeholders and the REDBLACKS can lead to increases in brand equity and value creation. In the end, the study suggested that future research should investigate the threat of co-destruction.
Keywords: co-creation; value; brand equity; football; value co-creation; brand co-creation; branding; marketing